Monitoring of Organochlorine Pesticides and Certain Heavy Metal Residues in Selected Vegetables and Fruits Collected from Eastern Libyan Markets - EL-Awami , Ifdial Omer; ELJarari, Rabaha M. (Al-Mukhtar Journal of Sciences, 2021)
Organochlorine pesticides are among the most common pollutants in the environment due to their high persistence, transportation throughout the food chain, and accumulation in the tissues of living organisms. This study was carried out owing to the lack of data on the residue levels of these pesticides and the heavy metals in vegetables and fruits that are present in the markets of the Eastern region of Libya, and to know the extent of their hazard to the health of the consumer by comparing them to the global Maximum Residue Limits. The results of analysis of some organochlorine pesticide residues (Chlordene, delta-HCH, gamma-HCH, beta-HCH, Dicofol, Endosulfan, P, P´-DDE, P´P´, DDD, Endrin, Heptachlor) and heavy metals in vegetable and fruit in Derna, El-Beida, and Al-Marg markets showed high significant differences between samples collected among seasons, where spring samples was more contaminated followed by autumn and summer. Also, Derna city was the most polluted area, followed by El-Beida and then Al-Marg. On the other hand, tomato samples contained the highest concentrations of lead and differed significantly from cucumbers, peppers, and lettuce. Zucchini was the least contaminated crop with lead but was the highest contaminated with zinc. By comparing pollution levels with the MRL globally, not all tested vegetables and fruits showed that they contained quantities higher than the internationally permissible limit in all regions and all seasons. Excluding Dicofol, Chlordene, and Heptachlor, which exceeded MRL in some vegetables and fruit such as tomato and zucchini.